Solitary pulmonary metastasis with cystic airspaces in colon cancer: A rare case report - Guo Kunliang; Li Yang; Chen Jian (Open Life Sciences)
This report presents a case of solitary pulmonary metastasis from colon cancer, characterized by cystic airspaces, which can mimic a second primary lung cancer (LC). Preoperative contrast-enhanced computed tomography in a patient with colon cancer revealed a pulmonary micronodule with a cystic cavity in the right upper lobe. The patient subsequently underwent left-sided hemicolectomy followed by six cycles of chemotherapy. During follow-up, computed tomography demonstrated resolution of the right upper lobe nodule. However, 36 months after chemotherapy, a solid nodule with cystic airspaces appeared in the right upper lobe, exhibiting marginal spiculation, traversing vessels, and enhancement, suggestive of cystic LC. Intraoperative frozen section analysis indicated features of intestinal adenocarcinoma. A right upper lobe wedge resection was performed, and postoperative histopathology confirmed the lesion as metastatic colon adenocarcinoma with cystic airspaces. Solitary pulmonary metastasis from colon cancer is relatively uncommon, particularly with cystic presentation. Clinicians and radiologists should maintain heightened suspicion in such atypical cases to avoid missed or delayed diagnoses.